Formulation and optimization of mucoadhesive bilayer buccal tablets of atenolol using simplex design method - Shirsand, SB; Suresh, Sarasija; Keshavshetti, GG; Swamy, PV; Reddy, P Vijay Prakash (International Journal of Pharmaceutical Investigation)
Introduction: In the present study, mucoadhesive buccal bilayer tablets of atenolol were fabricated with the objective of avoiding first pass metabolism and to improve its bioavailability with reduction in dosing frequency. Hence, the aim of this work was to design oral controlled release mucoadhesive tablets of atenolol and to optimize the drug release profile and bioadhesion. Materials and Methods: Bilayer buccal tablets of atenolol were prepared by direct compression method using simplex method of optimization to investigate the combined effect of hydroxypropyl methylcellulose 15 cps (X1), Carbopol (X2) and mannitol (X3); the in vitro drug release (Y1) and mucoadhesive strength (Y2) were taken as responses. The designed tablets were evaluated for various physical and biological parameters like drug content uniformity, in vitro drug release, short-term stability, and drug- excipient interactions (FTIR). Results: The formulation C containing hydroxypropyl methylcellulose 15 cps (10% w/w of matrix layer), Carbopol 934p (10% w/w of matrix layer) and mannitol (channeling agent, 40% w/w of matrix layer) was found to be promising. This formulation exhibited an in vitro drug release of 89.43% in 9 h along with satisfactory bioadhesion strength (7.20 g). Short-term stability studies on the promising formulation indicated that there are no significant changes in drug content and in vitro dissolution characteristics (P<0.05). IR spectroscopic studies indicated that there are no drug-excipient interactions.
Keywords: Atenolol; bioadhesive strength; mucoadhesive buccal tablet; simplex method of optimization; swelling index